Corpo, sensível e natureza na última ontologia de Merleau Ponty - Andrade, Eloisa Benvenutti De [UNIFESP] (2019)
In The visible and the invisible, posthumous work from Merleau-Ponty, for which the preproject was titled The Origin of Truth, is proposed to be a radical exam of our presence on the world. Under the perspective of the visible and invisible, Merleau-Ponty had intended to investigate a certain reversibility of the one who sees and of what is seen, covering, therefore, an original scenery: the expression wherever it is. We start from the hypothesis that the revision of the ideas of sensitive and nature, since The Structure of Behavior (1942) and Phenomenology of Perception (1945), had build one of the starting points to the refinement of that project. In this scope, the aim of this research is to present an investigation about the origins and consolidation of the ontological rehabilitation of the sensible, carried out by the author in the 50’s, and that could be illustrated by the passage of the conception of incarnated subject in the world to the idea of world-being or flesh. Our intent is to trace the steps that conducted Merleau-Ponty to the moment of generality of sensible in itself. Likewise, we seek to make evident that Merleau-Ponty’s project since the 40’s until the elaboration of The Visible and the Invisible (posthumously published in 1964) do not separate the tasks of phenomenology as philosophy from that of the ontology. As he himself wrote in The Philosopher and his Shadow, the ultimate purpose of phenomenology as philosophy of conscience is to comprehend its relation with the non-phenomenology. Thus, it is intended to show that there are no ruptures in theoretical evolution of the philosopher and also, consequently, that his reformulations can be understood as the inner unfolding of his theory culminating in something that we call the last ontology.